Cross-cultural adaptation and factor structure investigation of the Marital Forgiveness Scale - Sari, Endah Puspita; Helmi, Avin Fadilla; Febriani, Arum (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2024)
Forgiveness is essential in marriage as it can bring a sense of satisfaction to married life. This study aims to adapt and examine the factor structure of the Marital Forgiveness Scale (MFS), a forgiveness instrument in the context of marriage. After the process of adaptation to the Indonesian language and culture, validity and reliability tests were conducted, and a MIMIC model was developed. In an online and offline survey, 330 millennials (128 husbands, 202 wives, M-marriage age = 25.33, SD-marriage age = 3.12) completed the Indonesian version of the MFS. The validity test was conducted using confirmatory factor analysis, with the results showing that the values obtained were satisfactory (CFI & TLI ≥ .95; RMSEA = .06; SRMR < .08). The multidimensionality measurement of the Indonesian version of the MFS consists of two dimensions, a positive and a negative. The omega coefficient for the Indonesian version of the MFS is .694 (positive dimension) and .787 (negative dimension), indicating satisfactory reliability in the millennial sample. The results of the MIMIC model show that items 2 and 3 in the negative dimension have gender variance in the MFS. The scale is a suitable measure for evaluating individuals’ dispositional forgiveness in Indonesian millennial marital couples. It is hoped that the instrument will contribute to the advancement of the study of forgiveness in the marital context in Indonesia.